2016
DOI: 10.1080/08869634.2016.1244971
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dental occlusion on postural control and plantar pressure distribution

Abstract: Persistent dental parameters have no effect on postural sway. In addition, postural control and plantar pressure distribution have been found to be independent postural criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 42 publications
4
43
0
6
Order By: Relevance
“…Julia-Sanchez S. et al (2016) showed that mandibular position has a significant influence in the balance control; the body balance was better when dental occlusion was set in cotton rolls mandibular condition (with 8 mm thick cotton rolls placed between the two dental arches) in comparison with intercuspal position (achieved by clenching the teeth) [33]. Scharnweber et al (2016) after assessing 87 healthy male subjects noticed that blocking occlusion leads to sway reduction [34]. Our study recorded that in maximum intercuspation, the stabilometric parameters showed a better postural stability than in mandibular postural position.…”
Section: Discussionmentioning
confidence: 99%
“…Julia-Sanchez S. et al (2016) showed that mandibular position has a significant influence in the balance control; the body balance was better when dental occlusion was set in cotton rolls mandibular condition (with 8 mm thick cotton rolls placed between the two dental arches) in comparison with intercuspal position (achieved by clenching the teeth) [33]. Scharnweber et al (2016) after assessing 87 healthy male subjects noticed that blocking occlusion leads to sway reduction [34]. Our study recorded that in maximum intercuspation, the stabilometric parameters showed a better postural stability than in mandibular postural position.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a connection between postural control and the temporo-mandibular system can be assumed [5,9,11]. Whether an interference actually exists has been discussed for some time in literature [5,[11][12][13][14][15][16][17][18][19]; in some studies, correlations could be verified which proved changes in the postural control by different occlusion positions [5,12,13]. Accordingly, Ohlendorf et al [12] found a reduced frontal and sagittal extension of the body's centre of gravity by blocking the occlusion in contrast to the resting position.…”
Section: Introductionmentioning
confidence: 99%
“…However, this assumption should be analyzed in further studies. With regard to [23] and Scharnweber et al [24] confirm the increased percentage weight distribution between the forefoot and rearfoot, whereby the distribution between the two sides of the body is almost balanced. However, the left/right load ratio was found to be more balanced in handball players (50%: 50% distribution;) than in normal healthy individuals (46%:64%) [24].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to [23] and Scharnweber et al [24] confirm the increased percentage weight distribution between the forefoot and rearfoot, whereby the distribution between the two sides of the body is almost balanced. However, the left/right load ratio was found to be more balanced in handball players (50%: 50% distribution;) than in normal healthy individuals (46%:64%) [24]. The very good postural stability (ellipse) of young Polish goalkeepers of the Polish National Junior Handball as presented by Wilczyński [18], are very comparable with the present data of older male handball players.…”
Section: Discussionmentioning
confidence: 99%